Family Background, Parental Involvement, and Environmental Influences on Taiwanese Children - Hung, Chih-Lun (Alberta Journal of Educational Research, 2005)
This study examines to what extent fathers’ and mothers’ involvement in schooling is related to children’s school outcomes, taking into account differences in family social status, social structure, and children’s perceptions of their school learning environments. The findings suggested that (a) mothers were more involved in their children’s education than fathers; (b) children’s academic achievement is related to their family social status and social structure; (c) children’s self-concept is associated with their perceptions of school learning environments, parents’ aspirations, and parents’ involvement at home; and (d) the family social structure and school learning environment variables in the theoretical model mediate the relationships among family social status and children’s academic achievement and self-concept.